Practice Variation in Spontaneous Breathing Trial Performance and Reporting. (29th March 2016) - Godard, Stephanie; Herry, Christophe; Westergaard, Paul; Scales, Nathan; Brown, Samuel M.; Burns, Karen; Mehta, Sangeeta; Jacono, Frank J.; Kubelik, Dalibor; Maziak, Donna E.; Marshall, John; Martin, Claudio; et al.
Abstract : Background . Spontaneous breathing trials (SBTs) are standard of care in assessing extubation readiness; however, there are no universally accepted guidelines regarding their precise performance and reporting. Objective . To investigate variability in SBT practice across centres. Methods . Data from 680 patients undergoing 931 SBTs from eight North American centres from the Weaning and Variability Evaluation (WAVE) observational study were examined. SBT performance was analyzed with respect to ventilatory support, oxygen requirements, and sedation level using the Richmond Agitation Scale Score (RASS). The incidence of use of clinical extubation criteria and changes in physiologic parameters during an SBT were assessed. Results . The majority (80% and 78%) of SBTs used 5 cmH2 O of ventilator support, although there was variability. A significant range in oxygenation was observed. RASS scores were variable, with RASS 0 ranging from 29% to 86% and 22% of SBTs performed in sedated patients (RASS < −2). Clinical extubation criteria were heterogeneous among centres. On average, there was no change in physiological variables during SBTs. Conclusion . The present study highlights variation in SBT performance and documentation across and within sites. With their impact on the accuracy of outcome prediction, these results support efforts to further clarify and standardize optimal SBT technique.